Diabetic Ketoacidosis: Evaluation Of Therapeutic Outcomes, And Knowledge, Attitude And Practices Of Physicians And Pharmacists In Hospital Pulau Pinang - Usman, Atif (2013)
Incidence of Diabetes Mellitus (DM) and its associated acute co-morbidities is increasing. However, there is no Diabetic Ketoacidosis (DKA) treatment protocol in Malaysia at this point. There is no baseline data available for DKA in Malaysia as well. This study aims to record incidence rate of DKA and its treatment outcomes in Malaysian population. It is also intended to get an insight of knowledge, attitude and practices of healthcare professionals that are directly involved in management of DM and DKA. For first part, the study was done retrospectively at Hospital Pulau Pinang (HPP). DKA patient profiles were recorded by using universal sampling technique based on inclusion criteria and further analyzed using Statistical Package for Social Sciences (SPSS)® version 16. Of total 132 DKA patients, mean age of patients was 47.7 ± 16.3 years while most admissions were attributed to Malay patients (47%). DKA was more prevalent in T2DM (51.5%) patients followed by hypertension (54.5%) and dyslipidemia (43.0%). Most patients (61.4%) registered complaint of nausea and vomiting, and were accompanied with sepsis (31.9%) whereas attending physicians observed 83.3% patients to be dehydrated. Moreover, with mean blood glucose level at 30.4 ± 13.3 mmol · L-1, arterial pH at 7.15 ± 0.16, arterial bicarbonate at 9.7 ± 5.5 mmol · L-1 and ketones at 4.6 ± 1.7 mmol · L-1, chief DKA biochemical profiles rendered patients to be experiencing moderate episode of DKA, on average. It was also observed that newly diagnosed diabetes mellitus (NDDM) patients, deceased patients and ICU referred patients had more severe event of DKA than the rest of patients.